Prevalence, Risk Factors and Impact of Proteinuria-Associated Hypomagnesemia in Chronic Kidney Disease Patients: A Cross Sectional Study - Yasmeen Jameel, Ambash Farooq, Husnain Hashim, Shehrbano Batool, Ambreen Shams, Zareen Gul Rohi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Chronic kidney disease (CKD) patients who have hypomagnesemia are at greater risk of mortality and progression. A limited amount of data is available on the prevalence of hypomagnesemia in kidney-related risk factors and chronic kidney disease patients. The present study aimed to assess the Proteinuria-associated hypomagnesemia in chronic renal disease patients: prevalence, risk factors, and effect. Patients and Method: This cross-sectional study was carried out on 128 chronic kidney disease patients in the Medicine Department of Shifa International Hospital, Islamabad from January 2022 to August 2022. Patients were categorized into two groups based on estimated glomerular filtration rate (eGFR) are as follows: group-I composed of Proteinuric and group-II non-proteinuric. Prior to study conduction, the ethical committee approved the protocol. Patients with prior history of ileostomy, malignancy, chronic diarrhea, colostomy, and using magnesium based medications were excluded. Detailed history, physical examination, and investigations such as serum total magnesium level (mg/dl), serum sodium level (mg/dl), serum creatinine (mg/dl), and total cholesterol and triglycerides (mg/dl) were recorded. Hypomagnesemia was defined as a serum magnesium level < 1.8 mg/dL. Results: Of the total 128 CKD patients, there were 66 (51.6%) male and 62 (48.4%) females. Group I and II had 64 patients each. The overall mean age of group-I and group-II was 48.82±12.52 and 48.21±10.64 years respectively. The prevalence of hypomagnesemia (<1.8 mg/dL) in the proteinuric group was 20 (31.3%). Diabetic patients are more susceptible to hypomagnesemia. The incidence of diabetic, hypertensive, and both diabetic and hypertensive was 12 (60%), 3 (15%), and 5 (25%) respectively among 20 hypomagnesemia. Hypomagnesemia patients had higher CRP (46 mg/L), UACR (2064 mg/g), lower serum potassium (56.4%), lower mean hemoglobin levels (10.2 g/dL), and lower serum sodium (34.9%) as compared to normomagnesemic patients 12 mg/L, 810 mg/g, 24.8%, 11.25 g/dL, and 8.6% respectively. Conclusion: The present study found that there is an independent association between hypomagnesemia and proteinuria in non-dialysis CKD patients. Anemia and hyperparathyroidism are risk factors for inflammation and anemia in CKD patients pre-dialysis. Dietary magnesium supplementation and hypomagnesemia correction may retard proteinuria and CKD progression in CKD patients. Keywords: Chronic kidney disease, Proteinuria-associated hypomagnesemia, Risk factors